(untitled) (Fiep Bulletin - online, 2015)
Water is an essential element for the human being, but it could be a potential route of transmission of diseases by pathogenic microorganisms on serving all the contamination by fecal material. As important as the physical activity and a healthy diet, water intake with quality must be taken into account in our daily lives, in this sense, sought to evaluate the physico-chemical and microbiological quality of water intended for human consumption in waterers gymnastics academies in the city of Patos, Paraiba, Brazil. Water samples were collected from water fountains in 13 of the 26 academies registered by the Municipal health surveillance, being the samples analysed in the laboratory of food science health surveillance itself, following the provisions of Ordinance No. 2914/2011, the ANVISA (Ministry of health), which considers that water intended for human consumption must be free from Escherichia coli and total coliforms in 100 ml, color less than 15 UH, less than 5 NTU turbidity and pH between 6,0 and 9,5. The results obtained show a prevalence of 7,69%, for the period of September and October 2014.